The Competency Model Of Students At The Syekh Abdul Halim Hasan Binjai Institute - Sirait, Robin; Lubis, Syaiful Akhyar; Darmayanti, Nefi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Higher education institutions play a crucial role in preparing students to enter the workforce with competencies that align with their fields of study. This research was conducted to observe the development of student competencies at Syekh Abdul Halim Hasan Binjai Institute, particularly in the growth of both academic and non-academic skills. The activities aimed at developing student potential across various study programs, such as Islamic Religious Education, Sharia Banking, and Islamic Economic Law, are supported through collaboration with internal campus institutions. Both soft skills and hard skills of students have a significant impact on their success in the workforce. This study highlights the importance of a positive school climate and the relationship between students and lecturers in shaping academic competencies and scholarly personalities. Additionally, the Merdeka Belajar Kampus Merdeka (MBKM) program plays a vital role in competency development through internships, research, entrepreneurship, and other programs. This research employs a quantitative approach by collecting data from 104 students through questionnaires and analyzing them using reliability tests and hypothesis testing. The results show that a conducive school climate, as well as the development of soft skills and hard skills, contribute to improving student competencies relevant to the demands of the digital era and the job market.